APPLICATION OF SEGMENTATION IN DETERMINING POLICY ANALYSIS MARKETING STRATEGY - Setyobudi, Bambang (Entrepreneur, 2011)
AbstractIn fact the consumer supports all employees. The company produces goods or services aimed at consumers. They pay the benefits derived from the product or service that enjoyed. When the market runs perfectly, where consumers have many choices to meet their needs, then the producers should really find out what consumers needed. Knowing the consumers characteristics, it is necessary to have consumer research such as segmentation analysis using several approaches to the basic for segmentation such as geography, psychographics, benefits is consumers can be divided according to the profile or characteristics After Consumers can divided based on the profile or segment, respectively - were then the company can determine marketing strategies such as marketing mix (Marketing Mix).Keywords: Marketing concept, Market Segmentation, Market Potential HSBCAbstrakKonsumen mendukung perusahaan dalam memproduksi barang atau jasa yang ditujukan untuknya. Mereka siap membayar manfaat yang diperoleh dari produk atau jasa yang dinikmati. Ketika pasar berjalan sempurna, di mana konsumen memiliki banyak pilihan untuk memenuhi kebutuhan mereka, maka produsen harus benar-benar mengetahui apa yang konsumen butuhkan. Untuk mengetahui karakteristik konsumen, perlu mengadakan riset konsumen seperti analisis segmentasi yang menggunakan beberapa pendekatan sebagai dasar untuk segmentasi seperti geografi, psikografis, manfaatnya adalah konsumen dapat dibagi sesuai dengan profil atau karakteristik masing-masing. Setelah Konsumen dapat terbagi berdasarkan profil atau segmen, masing-masing - kemudian perusahaan dapat menentukan strategi pemasaran seperti bauran pemasaran (marketing Mix).Kata kunci: SarPemasaran, Segmentasi Pasar, Pasar HSBC Potensi